Simple Interrupted Microvascular Anastomosis: Review of Four Sutures Placement Sequences - Sullivan, Brianne; Zoppo, Michael; Yao, Alice; Henderson, Peter W. (Journal of Reconstructive Microsurgery Open, 2020)
Background Microsurgical anastomosis is a delicate, highly nuanced procedure that can be done in several different ways; the most basic approach to performing microsurgical anastomoses is by using simple interrupted sutures, but even within that approach, there are different sequences by which the sutures can be placed. To date, there is no review of these sequences and the advantages and disadvantages of each.Methods A PubMed search was performed in October 2019 that sought all published descriptions of simple interrupted microsurgery techniques. Keywords included were “microvascular anastomosis,” “microvascular anastomosis technique,” “simple interrupted,” and “microsurgery.”Results Four simple interrupted microsurgery techniques were identified: triangulation, 12 o'clock to 6 o'clock, posterior-wall-first, and 3 o'clock to 9 o'clock-side-side. Additionally, there is no uniform nomenclature that describes the techniques for simple interrupted microvascular anastomoses.Conclusion This study identified four distinct sequences for the placement of simple interrupted sutures for microsurgical anastomosis and the advantages and disadvantages of each, and for the first time described them utilizing standardized nomenclature.
Keywords: microvascular anastomosis; simple interrupted; microvascular anastomosis technique; microsurgery